A Comparative Analysis of Coronavirus Nucleocapsid (N) Proteins Reveals the SADS-CoV N Protein Antagonizes IFN-β Production by Inducing Ubiquitination of RIG-I - Liu, Yan; Liang, Qi-Zhang; Lu, Wan; Yang, Yong-Le; Chen, Ruiai; Huang, Yao-Wei; Wang, Bin (Frontiers in Immunology, 2021)
Coronaviruses (CoVs) are a known global threat, and most recently the ongoing COVID-19 pandemic has claimed more than 2 million human lives. Delays and interference with IFN responses are closely associated with the severity of disease caused by CoV infection. As the most abundant viral protein in infected cells just after the entry step, the CoV nucleocapsid (N) protein likely plays a key role in IFN interruption. We have conducted a comprehensive comparative analysis and report herein that the N proteins of representative human and animal CoVs from four different genera (swine acute diarrhea syndrome CoV [SADS-CoV], porcine epidemic diarrhea virus [PEDV], severe acute respiratory syndrome CoV [SARS-CoV], SARS-CoV-2, Middle East respiratory syndrome CoV [MERS-CoV], infectious bronchitis virus [IBV] and porcine deltacoronavirus [PDCoV]) suppress IFN responses by multiple strategies. In particular, we found that the N protein of SADS-CoV interacted with RIG-I independent of its RNA binding activity, mediating K27-, K48- and K63-linked ubiquitination of RIG-I and its subsequent proteasome-dependent degradation, thus inhibiting the host IFN response. These data provide insight into the interaction between CoVs and host, and offer new clues for the development of therapies against these important viruses.